Canine Rangeliosis: A Rare Case of Hyperparasitemia in the Acute Phase - Martins, Danieli Brolo; da Silva, Aleksandro Schaffer; de Oliveira, Evelyn; Labruna, Marcelo Bahia; Soares, João Fábio (Acta Scientiae Veterinariae, 2016)
Background: R. vitalii causes a remerging tick-borne disease known as rangeliosis. The parasite is not always identifable in blood smears, especially in the chronic phase of the disease. Low parasitemia levels have been observed in cases of rangeliosis caused by natural infection, even in acute situations, while hyperparasitemia has been reported only in acute experimental infection. This paper describes an unusual case of acute natural R. vitalii infection with hyperparasitemia. Case: The dog (a 12-year-old male German Shepherd) had presented apathy, dyschezia and hyporexia for three days prior to seeing the veterinarian, whose examination revealed discrete pale mucous membranes, soft bloody stools, hyperthermia, splenomegaly and lethargy. Numerous intra-erythrocytic forms, as well as free-living parasites compatible with R. vitalii and/or Babesia sp, were also found in the CBC (complete blood count), and the parasite load was estimated at 12 parasites/feld – x1000. After diagnosing hemoparasitosis from the blood smear, therapy was started immediately. After 18 days of treatment, the animal returned to the veterinary hospital showing visibly improved health. The dog’s mucous membranes showed normal coloration. A new CBC showed no intra-erythrocytic parasite in the blood smear. Some of the blood drawn during the animal’s frst examination was sent for DNA extraction. Two specifc TaqMan real-time PCR-based assays were performed to test for R. vitalii, and Ehrlichia canis. The sample was also tested for Babesia (Babesia canis and Babesia gibsoni), but tested positive only for R. vitalii. Discussion: Clinical signs related to the disease depend on its acute, subclinical, and chronic evolution, which may be reﬂected in clinical and pathological conditions. Our dog presented mild clinical signs of the disease, such as apathy, lethargy, hyporexia, hyperthermia, discrete pale mucous membranes, splenomegaly, dyschezia and soft bloody stools. In acute experimental cases, parasitemia increases progressively after inoculation, when R. vitalii becomes detectable in erythrocytes and leukocytes. In the chronic form of the disease, it is particularly rare to identify free-living forms of R. vitalii in the bloodstream or of the parasite in erythrocytes, and they are identifed in only in few cases of natural infection. The blood smear of our canine patient contained numerous parasitized cells, showing different shapes and sizes of the parasite, as well as a variable number of microorganisms parasitizing each cell. The number of parasitized erythrocytes was comparatively higher than that of leukocytes. This case report reveals that acute natural canine rangeliosis with hyper parasitemia is possible, indicating that the acute phase of the disease does not occur only in experimental cases. Although the animal showed nonspecifc clinical signs in the acute phase, the blood smear and PCR enabled the detection of the parasite. This leads us to suggest that, to ensure a better diagnosis, treatment and prognosis of rangeliosis, veterinarians should also determine whether the disease is in the acute or chronic stage. Keywords: Rangelia vitalii, natural acute phase, high parasitemia, dogs.